HUBUNGAN KEBIASAAN MEROKOK DENGAN KEJADIAN BENIGN PROSTAT HYPERPLASIA (BPH) DI RUANG PERAWATAN BEDAH RSUD. PROF. DR. H. ALOEI SABOE KOTA GORONTALO - Sabirin B. Syukur; Euis Hidayat (-, 2021)
BPH  constituting hyperplasia urgent periuretra gland network prostate to perifer. Its prevalence increases in line with age step-up on man. age end man 38 49 beresiko's years 8% suffers BPH and ages 60 70 jeopardy year increases to become 34%. Cause of BPH being known by ala must. But there is umpteen hypothesis names that BPH hand in glove bearing it with increasing dihidrotestosteron's rate (DHT) and process gets old .  To the effect in peneitian this is subject to be know wont relationship smokes with instance BPH. Research utilizes to methodic cross sectional   study.  Analisis is data did by analisis univariat and analisis is bivariate by use of quiz chi square is test . observational result wont smokes that in reference to instance BPH is custom smoking =12 erects perhari total 20 respondents (80,0%) with p value 0,001.There is relationship among custom smoking with instance BPH  at care room dissects RSUD. Prof. Dr. Hi. Aloei Saboe is Gorontalo's City